Queering medical education: systematically assessing LGBTQI health competency and implementing reform. Issue 1 (1st January 2018) - DeVita, Timothy; Bishop, Casey; Plankey, Michael
ABSTRACT: Lesbian, gay, bisexual, transgender, queer, and intersex (LGBTQI) individuals face well-established health disparities. American medical schools have been inconsistent in their training in the care of LGBTQI-identified patient, and many have not formally assessed their curriculums for content related to the care of LGBTQI-identified patients. From 2015 to 2016, the authors systematically evaluated Georgetown University School of Medicine's preclinical curriculum for its LGBTQI competency using video lecture capture, LGBTQI health competencies published by the American Association of Medical Colleges (AAMC) and learning objectives developed by Vanderbilt University. Based on the results of the curricular audit, the authors have created didactic content targeted at the identified curricular gaps that has been implemented throughout the preclinical curriculum at Georgetown. The curricular auditing process described here could be replicated at other medical schools, which would allow educators to develop targeted content to address unmet competencies. Abbreviations AAMC: Association of American Medical Colleges; LGBTQI: Lesbian, Gay, Bisexual, Transgender, Questioning, Intersex